Cardiovascular Disease in Women: Understanding Symptoms and Risk Factors - Keteepe-Arachi, Tracey; Sharma, Sanjay (European Cardiology Review, 2017)
Cardiovascular disease (CVD) in women remains under-diagnosed and undertreated due to the diagnostic challenge it presents, as well as the persisting attitude that CVD predominantly affects men. Gender-related risk factors have now been identified but there is a lack of clinical application, leading to the misdiagnosis and poor management of women with CVD. It is necessary to address gender-specific symptomatology and risk factors in order to optimise management and positively influence morbidity and mortality in this cohort of patients.